The Intelligent Technical Influence in Chat Generative Pre-Trained among Students for Modern Learning Traits - Kathiravan Ravichandran, B. Anita Virgin, Lucky Gupta, Aby John, Santiago Otero-Potosi, Álvaro Vargas-Chavarrea, Anurag Shrivastava (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper explores the influence of Chat Generative Pre-Trained, which is an Artificial Intelligence tool which provides text-based responses to user queries, on students’ learning motivation. The study involved 500 participants who were students in Medan, Indonesia. The research employed a quantitative approach, using surveys and questionnaires to gather data from the respondents. Previous research instruments were adapted with some modifications, which resulting in 10 items for the dependent and independent variables for each. Hypotheses were tested using linear regression, and classical assumption tests, such as multicollinearity, heteroscedasticity, and normality, were conducted. Descriptive statistics, like mean scores, were utilized to assess the extent of Chat GPT usage among students. The results showed that male students displayed a greater propensity for utilizing Chat GPT when compared to their female counterparts. Interestingly, younger students exhibited a higher degree of engagement with Chat GPT in contrast to their older peers. Additionally, the study uncovered a notable, positive, and statistically significant influence of Chat GPT usage on students’ motivation to learn.